UJI KETAHANAN ENAM VARIETAS PADI (Oryza sativa L.) TERHADAP KEKERINGAN SECARA MORFOLOGI DAN MOLEKULER - Susiyanti Susiyanti; Sulastri Isminingsih; Zahratul Millah; Widi Ayutami (Jurnal Agroekoteknologi, 2022)
Rice (Oryza sativa L.) is a staple crop that is always needed throughout the world, including Asia. Rice is one of the staple foods in Indonesia. One form of abiotic stress that becomes the main obstacle in rice production is drought stress. It is necessary to test rice varieties that are resistant to drought stress. This study aims to determine drought-resistant rice varieties based on SSR markers and to determine the morphological characteristics of drought-resistant rice. This research was carried out from January to April 2021 at the Laboratory of Physiology and Biotechnology, Faculty of Agriculture, Sultan Ageng Tirtayasa University and the Screen House of the Agricultural Technology Research Center Banten. The DNA isolation process in the molecular resistance test used the Doyle & Doyle (1990) method which used three SSR markers to detect drought resistance genes. Analysis of DNA bands using Gel Analyzer software, grouping analysis using the UPGMA method in NTSYS software. The results of the morphological study of six rice varieties on drought showed significant to very significant effects on the parameters of plant height (cm), root length (cm), number of tillers, and number of panicles. Molecular test results from three SSR primers on six rice varieties showed a high level of polymorphism with an average polymorphism information content (PIC) of 0.72 which was included in the very informative category and could be researched on drought resistance. The genetic similarity identified Jawara Hawara rice variety have drought resistance genes.